Counterclockwise maxillomandibular advancement surgery and disc repositioning: can condylar remodeling in the long-term follow-up be predicted?. Issue 12 (December 2017) - Gomes, L.R.; Cevidanes, L.H.; Gomes, M.R.; Ruellas, A.C.; Ryan, D.P.; Paniagua, B.; Wolford, L.M.; Gonçalves, J.R.
Abstract: This study investigated predictive risk factors of condylar remodeling changes after counterclockwise maxillomandibular advancement (CCW-MMA) and disc repositioning surgery. Forty-one female patients (75 condyles) treated with CCW-MMA and disc repositioning had cone beam computed tomography (CBCT) scans taken pre-surgery, immediately after surgery, and at an average 16 months post-surgery. Pre- and post-surgical three-dimensional models were superimposed using automated voxel-based registration on the cranial base to evaluate condylar displacements after surgery. Regional registration was performed to assess condylar remodeling in the follow-up period. Three-dimensional cephalometrics, shape correspondence (SPHARM-PDM), and volume measurements were applied to quantify changes. Pearson product–moment correlations and multiple regression analysis were performed. Highly statistically significant correlation showed that older patients were more susceptible to overall condylar volume reduction following CCW-MMA and disc repositioning ( P  ≤ 0.001). Weak but statistically significant correlations were observed between condylar remodeling changes in the follow-up period and pre-surgical facial characteristics, magnitude of the surgical procedure, and condylar displacement changes. After CCW-MMA and disc repositioning, the condyles moved mostly downwards and medially, and were rotated medially and counterclockwise; displacements in the opposite direction were correlated with a greater risk of condylar resorption. Moreover, positional changes with surgery were only weakly associated with remodeling in the follow-up period, suggesting that other risk factors may play a role in condylar resorption.